Women Leadership Performance in Learning Management at Private Madrasah Ibtidaiyah during the Covid-19 Pandemic in South Kalimantan - Salamah Salamah; Suriagiri Suriagiri; Muhammad Nur Effendi; Mudhiah Mudhiah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
This study aims to explore the role of female madrasah principals in education management, especially in the Ibtidaiyah madrasah environment. Qualitative research methods were conducted through observation, interviews, and documentation analysis in 13 districts of South Kalimantan province. The research focused on women's leadership roles in leveraging resources, building collaboration with the community, planning the curriculum, and utilizing technology in learning management. The results show that female madrasah principals play a key role in leveraging madrasah resources, building collaboration with the community, planning a responsive curriculum, and utilizing technology to improve learning. They are also active in developing an inclusive work culture, implementing effective supervision strategies, and creating open communication and active engagement within the madrasah environment. The findings provide an overview of the importance of women's leadership roles in managing education, confirming their contribution to creating an inclusive, innovative, and sustainable learning environment.